ANALISA KEBERHASILAN BISNIS KECIL - Soehari, Hartoyo (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
Small businesses play a vital role in economic development globally, contributing significantly to employment, innovation, and GDP growth. However, they face numerous challenges that affect their success rates. Understanding the factors influencing small business success is crucial for policymakers, entrepreneurs, and stakeholders to formulate effective strategies and support mechanisms. The study aims to determinne factors supporting the success of small cullinary business for 50 years. The trade is bakso, meat soup, in Pemalang District, Central Java, Indonesia. The study adopts qualitative method. Information were collected through an interview with the owner and families. The study found that enterpreneaur skill, raw materials, finance. Technology, and marketing, are pillar factors to succeed the business.